Structural and impedance spectroscopy characterization of Stannic oxide electronic system. (2023) - Sahoo, Limali; Bhuyan, S.; Tripathy, A.; Das, S.N.
Abstract: Stannic oxide (SnO2 ) is explored as one well-known material for many potential applications due to its unique electronic properties. The objective is to focus on structural and electrical characteristics of SnO2 electronic material, synthesized through the high-temperature solid-state principle. The sample has a tetragonal system, which is revealed by the X-ray diffraction technique. Different electrical parameters are comprehensively analyzed with the help of impedance spectrometer. The studied material has a relatively high dielectric constant and low tangent loss which furnish it as a suitable applicant for electronic applications.